2007
DOI: 10.1111/j.1469-8749.2005.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of postural adjustments in sitting position during the first half year of life

Abstract: Little is known about the development of postural adjustments during early ontogeny. We examined postural adjustments due to sudden perturbations during sitting in 40 healthy term infants (28 males, 12 females) assessed in groups of eight at 1, 2, 3, 4, and 5 months of age. Surface electromyograms of neck, trunk, and leg muscles were recorded while the infants were exposed to a random series of horizontal forward and backward displacements of the surface of support. Video recordings of spontaneous motor behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 26 publications
1
22
0
2
Order By: Relevance
“…The more precise deWnition resulted in substantially lower rates of direction-speciWcity. The studies of Hedberg et al (2004Hedberg et al ( , 2005 indicated that direction-speciWcitydeWned in the same precise manner as in the current study-is virtually always present in young sitting infants when their balance is grossly perturbed by a sudden movement of the support surface. The postural threat during reaching while lying supine or while sitting supported is considerably less.…”
Section: Discussionsupporting
confidence: 53%
“…The more precise deWnition resulted in substantially lower rates of direction-speciWcity. The studies of Hedberg et al (2004Hedberg et al ( , 2005 indicated that direction-speciWcitydeWned in the same precise manner as in the current study-is virtually always present in young sitting infants when their balance is grossly perturbed by a sudden movement of the support surface. The postural threat during reaching while lying supine or while sitting supported is considerably less.…”
Section: Discussionsupporting
confidence: 53%
“…O controle postural ou a preferência por formas específicas de recrutamento da estabilidade dependem da idade dos indivíduos e da natureza do desafio postural (HEDBERG et al, 2005;NU-NES;FONSECA;SCHEICHER, 2013;CIGNETTI et al, 2013). Crianças em idade escolar, por exemplo, não mostram uma preferência clara para a manutenção da estabilidade (CIGNETTI et al, 2013).…”
Section: Discussionunclassified
“…However, they found no organized patterns of muscle activities and suggested that neonates lack the ability to control their neck not only due to lack of muscle strength but also due to lack of coordinated muscle activities. Other studies have focused on the development of muscle synergies during reactive trunk control (following external perturbations) and muscle synergies during anticipatory balance (reaching movements) (Hedberg, Carlberg, Forssberg, & Algra, 2005;Hedberg, Forssberg, & Hadders-Algra, 2004). These studies suggested that infants as young as 1 month could generate direction specific postural adjustment in the neck and the trunk muscles during external perturbation.…”
Section: Emergence Of Independent Sittingmentioning
confidence: 99%
“…the level responsible for generating muscle synergies. However, these muscle synergies or adjustments were uncoordinated (Hedberg et al, 2005;Hedberg et al, 2004; M. Woollacott, Debu, & Mowatt, 1987). Three months is considered to be the age of functional transition, because, at this age, infants start to show spontaneous motor behavior related to postural activities.…”
Section: Emergence Of Independent Sittingmentioning
confidence: 99%
See 1 more Smart Citation